Pengenalan Huruf Anak Usia Dini Melalui Metode Intervensi Tadika Ceria - Natalia, Fenny; Ngelo, Lourentia Shearly Mahardhika; Tandya, Michael; Savistha, Ni Putu Pradnya Devani; Venissa, Shirley; Setiawan, Yuan Yovita (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2024)
This study aims to address the difficulties in letter recognition and enhance the confidence of students aged 3-5 years at TK/KB Al-Ikhlas Surabaya through the